Prévalence et facteurs associés aux candidoses vulvovaginales chez les femmes admises en consultation à l’Hôpital de Zone de Mènontin (Bénin) - FANOU, BRICE; Klotoé, Jean robert; DOUGNON, Tamègnon Victorien; MONTEIRO, Amamath (My University, 2022)
Introduction: vulvovaginal candidiasis (VVC) is a cosmopolitan, very frequent and recurrent condition due to disruption in vaginal balance and local immunity system. The purpose of this study is to determine the prevalence and factors associated with VVCs in women admitted to the Mènontin Hospital. Methods: we conducted a cross-sectional, descriptive and analytical study in the Department of Obstetrics and Gynaecology over the period March - August 2020. Sociodemographic, medical and gynecological data were collected from the medical records of 1336 subjects. Candida species were identified by conventional microbiological tests. Results: the prevalence of candidiasis was 56.25% in women with leucorrhea. It was not associated with sociodemographic factors such as age, marital status and BMI. Gestational age; the colour of the cervix and the amount and consistency of leucorrhoea were related to the occurrence of candidiasis. The most common species included Candida dubliniensis (36.11%) and Candida albicans (29.17%). Conclusion: eight species of candida are responsible for VVC in southern Benin. Knowing the associated factors allows for the implementation of appropriate control strategies.
Keywords: Candidose vulvovaginale; prévalence; facteurs associés; Bénin